Tensile Strength of Nerve Bridging Models Using Collagen Nerve Conduits - Hattori, Yusuke; Takeda, Shinsuke; Usami, Takuya; Shibata, Ryutaro; Takahashi, Hiroshi; Joyo, Yuji; Kawaguchi, Yohei; Okamoto, Hideki; Murakami, Hideki; Paholpak, Permsak; Ota, Hideyuki (Journal of Reconstructive Microsurgery, 2024)
Background In the treatment of peripheral nerve injuries with nerve defects, second-generation collagen-based conduits, such as Renerve® (Nipro, Osaka, Japan), have shown the potential for promoting nerve regeneration. However, there is concern related to the weak material properties. No previous studies have addressed the strength of the bridging model using collagen conduits. This study aimed to investigate the tensile strength and failure patterns in nerve defect models bridged with Renerve® conduits through biomechanical research.Methods Using fresh chicken sciatic nerves, we examined the maximum failure load of four groups: bridging models using Renerve® with one suture (group A), with two sutures (group B), with three sutures (group C), and end-to-end neurorrhaphy models with two sutures (group N). Each group had eight specimens. We also evaluated failure patterns of the specimens.Results Group N showed a significantly higher maximum failure load (0.96 ± 0.13 N) compared to groups A (0.23 ± 0.06 N, p < 0.0001), B (0.29 ± 0.05 N, p < 0.0001), and C (0.40 ± 0.10 N, p < 0.0001). Regarding failure patterns, all specimens in group A showed nerve-end dislocation from the conduit. Two specimens in group B and three specimens in group C failed due to circumferential cracks in the conduit. Six specimens in group B and five specimens in group C exhibited cutting out of sutures from the conduit.Conclusion This study suggests that the number of sutures in synthetic collagen nerve conduits has little effect on the maximum failure load. To take advantage of its biomaterial benefits, a period of postoperative range of motion restriction may be required.
Keywords: synthetic nerve conduits; tensile strength; collagen conduit; postoperative ROM restriction